2022
DOI: 10.1097/pas.0000000000001933
|View full text |Cite
|
Sign up to set email alerts
|

Embryonal Rhabdomyosarcoma of the Uterine Cervix

Abstract: Embryonal rhabdomyosarcoma of the uterine cervix (cERMS) is rare and frequently associated with DICER1 mutations. We report 94 tumors that arose in patients aged 7 to 59 (median = 23) years and presented with vaginal bleeding (52), protruding vaginal mass (17), cervical polyp (8), or expelled tumor fragments per vagina (5). Nine had DICER1 syndrome, 8 of whom had other syndromic manifestations including ovarian Sertoli-Leydig cell tumor ( 7), multinodular goiter (3), pleuropulmonary blastoma (2), pineoblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…These patients were younger and only 3 patients ERMS in cervix was the rst presentation of the syndrome. Identi cation of ERMS in a patient of any age, but particularly if young, should prompt referral for genetic testing and consideration of germline DICER1 testing [19,26]. In our series, only three of the patients have a test for DICER-1, but negative.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…These patients were younger and only 3 patients ERMS in cervix was the rst presentation of the syndrome. Identi cation of ERMS in a patient of any age, but particularly if young, should prompt referral for genetic testing and consideration of germline DICER1 testing [19,26]. In our series, only three of the patients have a test for DICER-1, but negative.…”
Section: Discussionmentioning
confidence: 83%
“…Five-year OS rate was 68.4%; factors associated with better OS were younger age, absence of distant metastasis, embryonal histology, negative lymph nodes, and performance of surgery. Devins et al [19] and Minard-Colin et al [20] also showed older age was associated with extrauterine recurrence and decreased disease-speci c survival. While there was no association between age and PFS or DSS in our series, maybe due to the small size of the sample.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In contrast, DICER1-associated sarcomas (SARC DICER1 and PIS DICER1) usually exhibit an overtly sarcomatous phenotype which is associated with frequent alterations in TP53, KRAS/NRAS and NF1 , high genomic index, as well as a global hypomethylation signature. In contrast to LGMT DICER1, DICER1-associated sarcomas may show a more aggressive clinical course 15 , 19 23 . Although the difference in the global methylomic profiles of these three classes may reflect their cell type composition, such as dominant epithelium component in LGMT DICER1, dominant sarcoma component in the other two classes and no epithelium in PIS DICER1, the identification of these DICER1-associated tumor classes from various anatomical sites will enable meaningful clinical trial stratification in the future and suggests that rational drug development addressing the differing molecular foundations of mesenchymal tumors with DICER1 alteration may be a plausible goal.…”
Section: Discussionmentioning
confidence: 95%